2023
DOI: 10.1186/s12964-023-01199-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of tRNA-derived small RNAs(tsRNAs) in the diagnosis and treatment of malignant tumours

Abstract: Malignant tumours area leading cause of death globally, accounting for approximately 13% of all deaths. A detailed understanding of the mechanism(s) of the occurrence and development of malignant tumours and identification of relevant therapeutic targets are therefore key to tumour treatment. tsRNAs(tRNA-derived small RNAs)—also known as TRFs (tRNA-derived fragments), tiRNAs (tRNA-derived stress-induced RNAs), tRNA halves, etc.—are a recently identified class of small noncoding RNAs that are generated from mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A unique strategy to confer resistance in such plant crops against viruses was envisioned via cytosolic RNase P (cytoRP) technology (Gobert et al, 2021), wherein plant PRORPs were re‐localized to accumulate in the cytoplasm to target TLSs, thereby disrupting viral replication. The tRNA‐derived small RNAs (tsRNAs), a class of small ncRNAs that occur due to processing activities of RNase P and similar processing enzymes, could serve as diagnostic markers to track disease progression (Mao et al, 2023). The disease‐associated pathogenic variants of the three human mt‐RNase P subunits lead to mitochondrial dysfunction in affected individuals displaying variable pleiotropic clinical phenotypes and is characterized by aberrant tRNA processing, insulin resistance, and oxidative phosphorylation (OXPHOS) defects (Chatfield et al, 2015; Hochberg et al, 2021; Hodgkinson et al, 2014; Jung et al, 2023; Metodiev et al, 2016; Rossetti et al, 2021; Sridhara, 2017).…”
Section: Applications Of Rnase Pmentioning
confidence: 99%
“…A unique strategy to confer resistance in such plant crops against viruses was envisioned via cytosolic RNase P (cytoRP) technology (Gobert et al, 2021), wherein plant PRORPs were re‐localized to accumulate in the cytoplasm to target TLSs, thereby disrupting viral replication. The tRNA‐derived small RNAs (tsRNAs), a class of small ncRNAs that occur due to processing activities of RNase P and similar processing enzymes, could serve as diagnostic markers to track disease progression (Mao et al, 2023). The disease‐associated pathogenic variants of the three human mt‐RNase P subunits lead to mitochondrial dysfunction in affected individuals displaying variable pleiotropic clinical phenotypes and is characterized by aberrant tRNA processing, insulin resistance, and oxidative phosphorylation (OXPHOS) defects (Chatfield et al, 2015; Hochberg et al, 2021; Hodgkinson et al, 2014; Jung et al, 2023; Metodiev et al, 2016; Rossetti et al, 2021; Sridhara, 2017).…”
Section: Applications Of Rnase Pmentioning
confidence: 99%
“…Novel among small non-coding RNAs, tsRNAs, derived from mature or pre-tRNAs, span 14 to 30 nucleotides ( Mao et al, 2023 ). These tsRNAs diverge into tRNA-derived fragments (tRFs) and tRNA-derived stress-induced RNAs (tiRNAs) ( Gao et al, 2022 ; Chen and Shen, 2021 ; Chu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs at the transcriptional level by binding transcription factors [11] and at the post-transcriptional level through RNA interference. Recent data have shown that tRFs are abnormally expressed in multiple malignant tumors and related to tumorigenesis [12]. For instance, tRFs may repress protein translation by binding a complementary mRNA target, resembling miRNAs [13].…”
Section: Introductionmentioning
confidence: 99%